The burden of femoral shaft fractures in Tanzania. Issue 7 (July 2019) - Conway, Devin; Albright, Patrick; Eliezer, Edmund; Haonga, Billy; Morshed, Saam; Shearer, David W.
Highlights: This study describes a novel, cross-sectional study of femur shaft fracture incidence in Tanzania based on empiric data. Femoral shaft fracture annual incidence rate ranged from 2.1 to 18.4 per 100, 000 people. Femur fracture:RTI ratios were a median low and high of 0.54 and 0.73. Common barriers to surgery reported during interviews included a lack of surgical implants, equipment, and personnel. This is the first study to report empiric data on femoral shaft fractures in Tanzania. Abstract: Background: Road traffic injuries disproportionately affect low- and middle-income countries (LMICs) and are associated with femur fractures that lead to long-term disability. Information about these injuries is crucial for appropriate healthcare resource allocation. The purpose of this study is to estimate the incidence of femoral shaft fractures in Tanzania and describe the unmet surgical burden. Methods: Study sites included six government hospitals across Tanzania. Investigators collected data from hospital admission and procedural logbooks to estimate femoral shaft fracture incidence and their treatment methods. Semi-quantitative interviews were conducted with relevant hospital personnel to validate estimates obtained from hospital records. Investigators gathered road traffic incident (RTI) statistics from national police reports and calculated femur fracture:RTI ratios. Results: Femoral shaft fracture annual incidence rate ranged from 2.1 to 18.4 per 100, 000 people. Median low and high femur fracture:RTI ratio were 0.54 and 0.73, respectively. At smaller hospitals, many patients (5–25%) were treated with traction, and a majority (70–90%) are referred to other centers. Barriers to surgery at each hospital include a lack of surgical implants, equipment, and personnel. Conclusions: The incidence rate is similar to previous estimations, and it is consistent with an increased femoral shaft fracture incidence in Tanzania when compared to higher income countries. The femur fracture:RTI ratio may be a valid tool for estimating femur fracture incidence rates. There is an unmet orthopaedic surgical burden for femur fractures treatment at rural hospitals in Tanzania, and the barriers to treatment could be targets for future interventions.